Effect of Surgical Approach on Pulmonary Function in Adolescent Idiopathic Scoliosis Patients: A Systemic Review and Meta-analysis. Issue 22 (15th November 2016) - Lee, Andy C.H.; Feger, Mark A.; Singla, Anuj; Abel, Mark F.
Abstract : Study Design: Systemic review and meta-analysis. Objective: To analyze the effect of spinal fusion and instrumentation for adolescent idiopathic scoliosis (AIS) on absolute pulmonary function test (PFTs). Summary of Background Data: Pulmonary function is correlated with severity of deformity in AIS patients and studies that have analyzed the effect of spinal fusion and instrumentation on PFTs for AIS have reported inconsistent results. There is a need to analyze the effect of spinal fusion on PFTs with stratification by surgical approach. Methods: Our analysis included 22 studies. Cohen's d effect sizes were calculated for absolute PFT outcome measures with 95% confidence intervals (CI). Meta-analyses were performed at each postoperative time frame for six homogeneous surgical approaches: (i) combined anterior release and posterior fusion with instrumentation; (ii) combined video assisted anterior release and posterior fusion with instrumentation without thoracoplasty; (iii) posterior fusion with instrumentation without thoracoplasty; (iv) anterior fusion with instrumentation and without thoracoplasty; (v) video assisted anterior fusion with instrumentation without thoracoplasty; and (vi) any scoliosis surgery with additional thoracoplasty. Results: Anterior spinal fusion with instrumentation, any scoliosis surgery with concomitant thoracoplasty, or video-assisted anterior fusion with instrumentation for AIS had similar absolute PFTs at their 2 year postoperative follow up compared with their preoperative PFTs (effect sizes ranging from −0.2–0.2 with all CI crossing "0"). Posterior spinal fusion with instrumentation (with or without an anterior release) demonstrated small to moderate increases in PFTs 2 years postoperatively (effect sizes ranging from 0.35–0.65 with all CI not crossing "0"). Conclusion: Anterior fusion with instrumentation, regardless of the approach, and any scoliosis surgery with concomitant thoracoplasty do not lead to significant change in pulmonary functions 2 year after surgery. Posterior spinal fusion with instrumentation (with or without an anterior release) resulted in small to moderate increases in PFTs. Level of Evidence: N/A